Urban space and the power of language: the stigmatization of the faubourg in 19th century France - Merriman, John (1999)
With the growth of French cities in the 19th century, a discourse of stigmatization developed in response to the economic and social evolution of the urban periphery. The faubourgs, which had already for some time made urban elites uneasy, were stigmatized as the locus of people (and activities) unwanted in the center city. They were expelled to the periphery (with the Haussmannization of Paris providing the classisc case). At the same time, the social fear of the people of the faubourgs became increasingly linked with political fear, indeed well before the end of the century, when the faubourgs (not all of them, of course, as Versailles and some others were quite different) were evolving into "the suburbs", those of Paris, above all, but in many provincial towns and cities as well, and especially when certain faubourgs and suburbs began to mount a challenge to the politics of the center city. Here we are joining the effort to establish the historical origins of a true discourse and vocabulary of the stigmatization of the urban periphery of French cities, so marked today, and place them in the middle decades of the 19th century. - Reproduced
Keywords: Urban spaces - France; Urban spaces